Functioning of local and regional units in contemporary economic conditions. Chosen aspects - Korenik, Stanisław; Rogowska, Małgorzata (Funkcjonowanie jednostek lokalnych i regionalnych we współczesnych realiach gospodarczych. Wybrane aspekty, 2017)
Contemporary economy can be characterized by a simultaneous lack of space, growth of international exchange, growing importance of international corporations and internationalization of financial phenomena, which is undoubtedly favoured by the development of IT techniques. At the same time, along with the development of the knowledge-based economy as a new economic paradigm, the importance of the so-called spatial development increases in the development of spatial units, new factors that primarily include the quality of human capital, specific ICT infrastructure and the quality of business environment institutions. Territorial units must behave flexibly and be part of new trends. The article presents loose considerations on contemporary socio-economic conditions affecting the development of local and regional systems.
Biblioteka Regionalisty, 2017, Nr 17, s. 67-74
Keywords: local development; regional development; modern economy; rozwój lokalny; rozwój regionalny; współczesna gospodarka